1982
DOI: 10.1139/o82-015
|View full text |Cite
|
Sign up to set email alerts
|

The purification and characterization of a phospholipase A2 activity from the 106 000 × g pellet (microsomal fraction) of bovine brain acting on phosphatidylinositol

Abstract: A phospholipase A2 acting on phosphatidylinositol (PI) has been purified from the 106 000 × g pellet (microsomal fraction) of bovine grey matter. The purification steps included extraction with Triton X-100 (0.05%), ammonium sulfate fractionation (20–50% fraction), consecutive column chromatographic runs on Sephadex G-200 and DEAE-Sephacel, and preparative gel electrophoresis (on 10.5% polyacrylamide gel). These steps achieved a purification of 1614 times. The purified enzyme ran as a single band on sodium dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…PLA2 activity was solubilized with 0.05% Triton X-100 and purified using multiple-column chromatographic procedures giving a 1,600-fold purification over crude homogenate. The activity of the purified enzyme was highest with phosphatidylinositol (Ptdlns; 100%), compared with PtdCho (62%), phosphatidic acid (PtdOH; 33%), phosphatidylethanolamine (PtdEtn; 25%), and phosphatidylserine (21%) (Gray and Strickland, 1982). The purified enzyme was stimulated at high Ca 2~concentrations (5 mM) and had a molecular mass of 18.5 kDa and a pH optimum of 7.4 (Table 1) (Gray and Strickland, 1982).…”
Section: Occurrence Multiplicity and Properties Of Brain Pla2mentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2 activity was solubilized with 0.05% Triton X-100 and purified using multiple-column chromatographic procedures giving a 1,600-fold purification over crude homogenate. The activity of the purified enzyme was highest with phosphatidylinositol (Ptdlns; 100%), compared with PtdCho (62%), phosphatidic acid (PtdOH; 33%), phosphatidylethanolamine (PtdEtn; 25%), and phosphatidylserine (21%) (Gray and Strickland, 1982). The purified enzyme was stimulated at high Ca 2~concentrations (5 mM) and had a molecular mass of 18.5 kDa and a pH optimum of 7.4 (Table 1) (Gray and Strickland, 1982).…”
Section: Occurrence Multiplicity and Properties Of Brain Pla2mentioning
confidence: 99%
“…PLA2 activities were then determined in rat brain synaptosomes and in neuronal and glial cell preparations obtained from rabbit brain (Woelk et al, 1978). Since then, different isoforms of PLA2 have been partially purified and characterized (Gray and Strickland, 1982;Hirashima et al, 1992;Nègre-Aminou and Pfenninger, 1993;Nègre-Aminou et a!., 1996). Ca 2 k-dependent PLA 2 The purification and characterization of PLA2 were started with bovine brain gray matter microsomes.…”
Section: Occurrence Multiplicity and Properties Of Brain Pla2mentioning
confidence: 99%
“…The central nervous system (CNS) appears to contain multiple PLA 2 types, including calcium-dependent and calcium-independent forms of various molecular masses and substrate specificities (Gray and Strickland, 1982;Ross et al, 1995;Thomson and Clark, 1995;Hirashima et al, 1992;Yang et al, 1996). Which cells in the brain express which particular PLA 2 isoform is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies with mice deficient for both PLA 2 receptor and group IIA sPLA 2 demonstrated a potential role of group IB sPLA 2 /PLA 2 receptor-mediated responses in the progression of endotoxic shock, because the knock-out mice exhibit resistance to endotoxininduced lethality with reduced plasma levels of inflammatory cytokines (37). Besides previously identified sPLA 2 s, other low molecular weight PLA 2 s have been detected in various tissues including the brain and lung (38), suggesting the presence of novel sPLA 2 s that might play a compensatory role for the deficiency in group IIA sPLA 2 or an independently functional role in the inflammatory processes.…”
mentioning
confidence: 98%